ضوابط إبرام الإتفاقيات بين شركة المساهمة والقائمين بإدارتها - العابد, توفيق; بوساحة, نجاة (Revue des Sciences Juridiques et Politiques, 2021)
يُسلِط هذا المقال الضوء على الضوابط التي تضمنها القانون التجاري الجزائري، في مجال إبرام الاتفاقيات بين شركة المساهمة والقائمين بإدارتها، بغية التوصل إلى معرفة مدى نجاعتها في ضمان حماية الشركة من العواقب الناجمة عن تعارض المصالح، وذلك من خلال التعرض بالوصف والتحليل للصور والإجراءات التي أقرتها النصوص القانونية الناظمة، بالإضافة إلى ما تم اعتماده في بعض التشريعات المقارنة. وقد خلصت الدراسة إلى أن المشرع الجزائري لم يحقق توازناً فعلياً بين سلطتي الإدارة والرقابة، نظرا لاعتماده على المراقبة البعدية التي أثبتت التجارب العملية عدم فعاليتها في معالجة قصور نظرية الوكالة. The article sheds light on the regulations of making agreements between the joint-stock company and its administrators in Algerian commercial law. In order to find out their effectiveness in ensuring that the company is protected from the consequences of conflicting interests, the images and procedures which are approved by the legal texts and have been adopted by comparative legislation were described and analyzed. The study concluded that the Algerian legislator did not achieve an effective balance between the authority of administration and that of censorship, due to the reliance on posteriori control, which practical experiences have proven ineffective in addressing the deficiencies of the agency theory.
Keywords: Administrators; Agreements; Conflicting interests; Joint-stock company; Regulations